Comites Villageois Et Problématique De La Gestion Des Points D’eau Dans L’arrondissement De Bayangam (Ouest-Cameroun) - Tchekote, Hervé; Poka, Angeline Noufin; Mbarga, Fridolin Brice Nicolas Atekoa (European Scientific Journal, ESJ, 2018)
Households in Bayangam district in the west high land of Cameroon face many difficulties, one of the most important of which is access to water resources in terms of quality and quantity. Most people travel long distances in search of water, which is sometimes not reassuring. However, many boreholes as well as Village Committees of Water Point Management (CVGPE) have been set up in this locality. From this observation, the hypothesis according to which the existence of the Village Management Committees does not ensure the sustainable management of the water points in Bayangam was formulated. To verify this hypothesis, literature searches as well as direct observations in the study area were first conducted. Then, survey questionnaires from 150 households were administered. Finally, interviews with 14 resource persons representing the key players were conducted. The results of the study show that many CVGPEs have been established in the Bayangam district in recent decades, with the aim of ensuring better management of the water points set up by a multitude of stakeholders. However, most of these water points are almost non-functional or poorly maintained. Faced with this situation, it is important: to carry out a complete diagnosis of the works for a rehabilitation, to improve the choice of the members for more efficient services, to encourage a thorough involvement of the beneficiaries and a more remarkable support of the Bayangam commune to manage water points for a sustainable supply of populations.